1996
DOI: 10.1152/jappl.1996.80.4.1270
|View full text |Cite
|
Sign up to set email alerts
|

Influence of global inspiratory muscle fatigue on breathing during exercise

Abstract: We evaluated the effect of global inspiratory muscle fatigue (GF) on respiratory muscle control during exercise at 30, 60, and 90% of maximal power output in normal subjects. Fatigue was induced by breathing against a high inspiratory resistance until exhaustion. Esophageal and gastric pressures, anteroposterior displacement of the rib cage and abdomen, breathing pattern, and perceived breathlessness were measured. Induction of GF had no effect on the ventilatory parameters during mild and moderate exercise. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 0 publications
5
49
0
Order By: Relevance
“…5) is more likely a consequence, rather than a cause, of the reduced speed throughout the entire EMF-EX. Indeed, HR relative to speed did not diVer between EMF-EX and CON-EX, and previous studies have shown that induction of IMF did not modify HR during subsequent exercise at a given power output (Mador and Acevedo 1991;Sliwinski et al 1996).…”
Section: Methodological Aspectsmentioning
confidence: 58%
“…5) is more likely a consequence, rather than a cause, of the reduced speed throughout the entire EMF-EX. Indeed, HR relative to speed did not diVer between EMF-EX and CON-EX, and previous studies have shown that induction of IMF did not modify HR during subsequent exercise at a given power output (Mador and Acevedo 1991;Sliwinski et al 1996).…”
Section: Methodological Aspectsmentioning
confidence: 58%
“…Flow resistive loads have been used to target specifically the inspiratory or expiratory muscles, whereas voluntary hyperpnea has been used to target globally the respiratory muscles. Using these procedures, exercise capacity has been shown to either decrease (323,341,517,538) or not change (136,487,491). However, a problem with "prefatigue" studies, is that respiratory muscle fatigue is generally either not assessed (136,341,491) or not quantified objectively using direct, effort independent techniques (323, 538).…”
Section: Consequences For Exercise Performancementioning
confidence: 99%
“…Fatigue of inspiratory or expiratory muscles can be produced using resistive loads, while global respiratory muscle fatigue can be achieved using voluntary hyperpnea. Prefatigue studies have shown either a significant decrease (69,79,132) or no change (24,113,118) in performance during subsequent heavy exercise. However, a problem with some of these studies is that respiratory muscle fatigue was not assessed (24,79,118) or was not quantified objectively using nerve stimulation techniques (69,132).…”
Section: Functional Consequences Of Respiratory Muscle Fatiguementioning
confidence: 99%